Retail banking in the electronic age : the law and economics of electronic funds transfer - Baxter, William F.; Cootner, Paul H.; Scott, Kenneth E. (Montclair, N.J. : Allanheld, Osmun, 1977)
This study examines various aspects of electronic funds transfer systems and their implications for retail banking in the United States.
Includes bibliographical references and index.
Loans
osc 27/3/18
Keywords: Electronic funds transfers; Banks and banking; Banking law